Effects of continuous nursing on gastrointestinal function with ileal cystostomy - Zhou, Jinyuan; An, Xushu; Chen, Xueting; Ding, Dexin (Frontiers in Surgery, 2025)
ObjectiveThe importance and value of continuous care for patients after ileal cystostomy is established, and relevant experience to provide references for clinical practice is summarized in this study.MethodsThis study was conducted at the Affiliated Tumor Hospital of Harbin Medical University, China, from July 2020 to July 2022. A total of 40 subjects were divided into a routine nursing group, which received routine perioperative health education, and stoma nursing was given at the bedside after the operation and followed up within one week after discharge, and a continuous nursing group, which was given continuous nursing based on routine nursing measures. The two groups’ quality of life (QoL), stoma complications, Patient satisfaction, gastrointestinal function, and other indicators were evaluated.ResultsAll the scores linked to the QoL in the continuous nursing group were markedly better than that in the routine nursing group, and the divergence was statistically notable. The continuous nursing group had fewer stoma complications, higher Patient satisfaction, and better gastrointestinal function.ConclusionContinuous nursing can markedly enhance patients’ QoL, lessen complications, and enhance patients’ satisfaction and gastrointestinal function. It has significant value and practical importance.